Buttercup sunshine and the zombies of dooooom - Mulhern, Colin (West Sussex, RH : Maverick Arts Publishing Ltd., 2018)
Briar's Cove is the nicest, safest, sweetest place there ever was, where nothing bad ever happens. Until a fallen star causes the dead to rise from their graves. Together with her beloved Granny, and armed only with a vacuum cleaner and a bag of wool, Buttercup Sunshine must make a stand against the approaching army of the undead.
Keywords: Zombies -- Fiction; Juvenile fiction; Humorous stories